Comparison of Three Energy-Saving Strategies Based on Models Established for In Situ Gas Thermal Remediation of Contaminated Soil. (17th January 2022) - Zhang, Haijing; Zhang, Xiang; Yin, Yao; Liu, Gaojie; Zhu, Yu; Tan, Xuejun; Huang, Yuan
Abstract : Soil pollution has become an issue of concern with the development of industrialization. In situ gas thermal remediation is a suitable remediation technology for heavily organic contaminated soil, yet its high energy consumption limits the application. In this study, three energy-saving strategies, off-gas burn-back mode, heat-returning mode, and air-preheating mode, were proposed, and their natural gas consumption and energy utilization ratio were analysed. A mathematical model was established for the heat and mass transfer in unsaturated soil by employing conjugate heat transfer. The temperature of the soil and flue gas, and the concentration of components in the soil and off-gas were simulated, which indicated the thermal behavior of the contaminated soil and the timing for operation control. Models of burners were also developed under different energy-saving modes for energy analysis. By comparing the basic method, adopting the off-gas burn-back mode obtained an energy-saving effect of 3.37%, which relied on the content and calorific value of the pollutant in the off-gas. Under combustion air-preheating ratios of 0.5 and 1.0, natural gas could only be saved by 13.56% and 18.88%, respectively. In general, the most effective energy-saving measure was the heat-returning mode, by which 21.44% of natural gas could be saved when the reflux ratio of the flue gas was 0.5.